Thyroid Hormones in Hemolymph of Red King Crabs from the Barents Sea - Alexander G. Dvoretsky; Elena V. Tipisova; Viktoria A. Alikina; Aleksandra E. Elfimova; Vladimir G. Dvoretsky (Animals, 2022)
Only a few studies have reported the presence and levels of thyroid hormones in invertebrates. At the same time, the administration of these hormones has been shown to be a profitable method for inducing growth in crustaceans. Knowledge of thyroid hormone concentrations is required to involve this approach in crustacean aquaculture. For this reason, we examined hemolymph samples of the invasive red king crab Paralithodes camtschaticus from the Barents Sea population for the levels of triiodothyronine (T3) and thyroxine (T4). Radioimmunoassays indicated that T3 ranged from 0.26 to 1.55 μg dL–1, whereas T4 varied from 52 to 203 μg dL–1. Adult crabs demonstrated higher levels of T3 than juveniles, while juvenile crabs had higher levels of T4 in comparison to larger conspecifics. The thyroxine levels were consistent throughout the study period. In contrast, significant seasonal variations were found for T3. In immature crabs, the maximum concentration was found in October, whereas in adult crabs, the highest level of T3 was registered in August. Most likely, these results are explained by changes in physiological conditions of the crabs associated with their molting calendar and migration activity. Our data may have important implications for aquaculture of Paralithodes camtschaticus in the Barents Sea.